PENGARUH PENGGUNAAN BATTERY LIFE EXTENDER TECHNOLOGY TERHADAP TEMPERATUR CHARGING DAN BERAT ELEKTROLIT PADA YUASA LEAD ACID BATTERY TIPE LIQUID VENTED 12V 5Ah - Indra Angga Wibowo; C. Sudibyo; Basori Basori (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2014)
The purpose of this research: (1) To investigate battery temperature during charging using batterycharger and electrolyte weight reduction in Yuasa lead acid battery 12V 5Ah liquid vented type before givingbattery life extender technology (Vitta-Q battery vitamin). (2) To investigate battery temperature duringcharging using battery charger and electrolyte weight reduction in Yuasa lead acid battery 12V 5Ah liquidvented type after giving Vitta-Q battery vitamin.This research was used experimental method. The experiment was conducted at the Laboratory ofAutomotive Mechanical Engineering Education Program, the Laboratory of Mechanical Civil EducationProgram, JPTK FKIP UNS Surakarta and the Laboratory of Mathematics and Natural Sciences FMIPA UNSSurakarta which addressed at Ahmad Yani 200 Kartasura. The instruments which used to test were DeltaDT.115K battery charger, Mettler Toledo digital balance, and Perkin Elmer UV/VIS Spectrometer. The researchpopulation were Yuasa 12V 5Ah battery with code number YB5L-B and the research sample were 6 Yuasa 12V5Ah batteries with code number YB5L-B with lifetime of approximately 2 years or 20.000 miles. Thecomparative study descriptive investigation methode was used to analyse the data.Based on this research can be concluded: (1) The measurement on Yuasa lead acid battery 12V 5Ahliquid vented type before giving Vitta-Q battery vitamin during charging using battery charger resulted thetemperature 49 oC and weight of electrolyte 209.5 gr in 230.0 gr electrolytes. (2) The measurement on Yuasalead acid battery 12V 5Ah liquid vented type after giving 2 ml of Vitta - Q battery vitamin per cell duringcharging using battery charger resulted the lowest temperature 40.3 oC and weight of electrolyte 216.4 gr in230.0 gr electrolytes. (3) The measurement on Yuasa lead acid battery 12V 5Ah liquid vented type after giving3.5 ml of Vitta - Q battery vitamin per cell during charging using battery charger resulted the highesttemperature 49.8 oC and weight of electrolyte 208.1 gr in 230.0 gr electrolytes